Loss of the Sympathetic Signal Produces Sterile Inflammation of the Prostate - Hu, Hao; Cui, Yiwen; Yang, Jing; Cao, Ying (Frontiers in Molecular Neuroscience, 2022)
Neural innervations exert essential roles in the prostate. However, spatial distribution and regulatory function of such neural inputs remain incompletely characterized. Here, we exploited the advanced whole-tissue immunolabeling and optical clearing technique to assess the 3D anatomy of autonomic innervations in the mouse and human prostate for the first time. We observed that sympathetic and parasympathetic inputs in the mouse prostate remained unaffected during castration-induced tissue regression. However, the pharmacologic destruction of sympathetic innervations in the mouse prostate led to sterile inflammation of the tissue, mimicking the disease condition of chronic nonbacterial prostatitis. Also, the genetic ablation of sympathetic inputs produced a similar inflammatory response. Furthermore, we showed that treatment of the specific β2-adrenergic receptor agonists could effectively mitigate the prostate inflammation caused by such sympathetic loss. Together, these results have elucidated the new immunomodulatory function of the sympathetic signal via the β2-adrenergic receptor in prostate inflammatory disease.